2015
DOI: 10.3389/fpsyt.2015.00122
|View full text |Cite
|
Sign up to set email alerts
|

Attentional Profiles and White Matter Correlates in Attention-Deficit/Hyperactivity Disorder Predominantly Inattentive Type

Abstract: Attention-deficit/hyperactivity disorder (ADHD) is a widely studied neurodevelopmental disorder. It is a highly heterogeneous condition, encompassing different types of expression. The predominantly inattentive type is the most prevalent and the most stable over the lifetime, yet it is the least-studied presentation. To increase understanding of its cognitive profile, 29 children with attention-deficit/hyperactivity disorder of predominantly inattentive type (ADHD-I) and 29 matched controls, aged 7–15 years, h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 63 publications
2
12
0
1
Order By: Relevance
“…Lower IQ scores in ADHD comparing to neurotypicals are consistent with previous studies [Biederman et al, , 2009. In ADHD, scores are likely results of suboptimal test-taking behavior and attention problems indicative of the disease [Dennis et al, 2009;Jepsen et al, 2009;Rossi et al, 2015] and thus correction for IQ might introduce a possible bias to the findings [Dennis et al, 2009]. As such, primary analyses were not adjusted for IQ, although an exploratory analysis adjusted for both age and IQ was also conducted and revealed similar conclusions as primary analysis (see Supporting Information).…”
Section: Limitationssupporting
confidence: 82%
See 1 more Smart Citation
“…Lower IQ scores in ADHD comparing to neurotypicals are consistent with previous studies [Biederman et al, , 2009. In ADHD, scores are likely results of suboptimal test-taking behavior and attention problems indicative of the disease [Dennis et al, 2009;Jepsen et al, 2009;Rossi et al, 2015] and thus correction for IQ might introduce a possible bias to the findings [Dennis et al, 2009]. As such, primary analyses were not adjusted for IQ, although an exploratory analysis adjusted for both age and IQ was also conducted and revealed similar conclusions as primary analysis (see Supporting Information).…”
Section: Limitationssupporting
confidence: 82%
“…Concepts of ADHD-PI and ADHD-C Particular involvement of fronto-limbic pathways (cingulum bundle) in ADHD-C aligns with previous DTI [Lei et al, 2014;Nagel et al, 2011] and resting-state findings [Fair et al, 2012] and might represent a structural substrate of executive functions and sustained attention deficits [Chiang et al, 2015;Kubicki et al, 2003] in ADHD-C. On the other hand, ADHD-PI preferentially demonstrated disturbances in fronto-striato-thalamic circuits that are implicated in cognitive control [Fair et al, 2012], processing speed [Rossi et al, 2015], and selective attention [Wright et al, 2015], indicative of ADHD-PI. In addition, disruptions in occipito-temporal, fronto-limbic and corticospinal connections might add to other features of abnormal executive functioning in ADHD-PI [Chuang et al, 2013;Kaiser et al, 2014].…”
Section: Importance In Current Neuropsychologicalsupporting
confidence: 78%
“…However, the high heterogeneity observed in the disorder has resulted in inconsistent findings among different studies. Indeed, a previous analysis conducted with the same sample used in the present study did not reveal any differences in FA measurements when ADHD and TD individuals were compared (14). …”
Section: Introductionmentioning
confidence: 44%
“…As mentioned before, a previous analysis conducted with the same sample of the current study (14) compared the FA values of the same 20 fiber tracts, grouping the subjects according to their original diagnosis group (ADHD-I vs TD). Contrasting with the current results, in the previous study no significant differences were found between the groups.…”
Section: Discussionmentioning
confidence: 99%
“…Apesar de não encontrarmos diferença significante entre os grupos no presente estudo, nosso resultado está em concordância com o estudo de Semeijn et al120 quanto a correlação reação, verificou-se uma média maior no grupo TDAH, significando um desempenho mais prejudicado, porém as diferenças são pequenas, não apresentando significância estatística. A ausência de diferenciação entre os grupos sobre as médias do tempo de reação total (CPT-Hit RT) está consistente com a maioria de estudos de medidas de tempo de reação (total) com amostras mais jovens, como visto nos estudos de Gmehlin et al34 , Kuntsi e Klein 31 e na revisão meta-analítica de Kofler et al33 , embora alguns estudos8,70 encontraram um pior desempenho no tempo de reação total (RT) no grupo TDAH utilizando o teste CPT. Por outro lado, a ausência de diferenciação entre os grupos sobre a variabilidade no tempo de reação verificado pelo CPT se difere do encontrado na maioria da literatura8,30,31,33,34 , os quais indicam uma maior variabilidade no tempo de reação e sugerem essa diferenciação como um possível marcador para o TDAH em amostras mais jovens.…”
unclassified